Do Job Boredom and Distress Influence Self-Report Individual Work Performance? Case Study in an Indonesia Muslim Fashion Industry - Auditya Purwandini Sutarto; Nailul Izzah (Jurnal Optimasi Sistem Industri, 2022)
A creative and innovative workforce is a key determinant of the sustainability of the fashion industry in a highly competitive market. Such characteristics have been linked to employees’ well-being. This study aimed at examining to what extent the employees’ boredom, stress, and work performance levels in a medium-scale Muslim fashion Industry. We employed a cross-sectional study design by administering a set of questionnaires consisting of the Dutch Boredom Scale; Depression, Anxiety, and Stress Scale; and Individual Work Performance in a total sampling of 75 female workers. The association between key variables and demographic factors was analyzed using non-parametric tests while the relationship between boredom, stress, and work performance was analyzed using the regression. Less-educated employees reported more stress and lower work performance while their boredom levels were similar, compared to their counterparts. Job boredom and stress were higher among newly hired employees but no significant difference in self-reported productivity between the two job experience groups was observed. There are also no differences in job boredom, stress, and work performance between sales and non-sales groups. Our regression model shows that job boredom and stress were significant predictors to work performance after controlling age, education, job experience, and type of occupations. These findings support the importance of improving employees’ well-being for better individual performance which may, in turn, lead to any tangible organizational outcomes. Regardless of the case study design, our study may provide insights for other industrial sectors and beyond the context of small and medium enterprises.